2019
DOI: 10.3390/polym11122109
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Treatment of Polymer Powder as an Effective Tool to Functionalize Polymers: Case Study Application on an Amphiphilic Polyurethane

Abstract: Plasma treatment is a widely applied, easy, fast, and highly reproducible surface modification technique. In this work powder plasma treatment was exploited to expose carboxylic groups along the backbone of a water soluble polymer. Specifically, a custom-made amphiphilic poly(ether urethane) containing Poloxamer® 407 blocks (Mw = 54,000 Da) was first synthesized and its powders were plasma treated in the presence of Acrylic Acid vapor. To maximize –COOH group exposure while preventing polymer degradation, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…In fact, at 37 • C both NHP407 and SHP407 systems exhibited ω G /G crossover values lower than 0.1 rad/s and turned out to be in the gel state, although a not complete gel development was achieved. This result can be correlated to the presence in SHP407-based system of a higher number of hydrogen bonds due to the exposure of free -NH 2 groups, which contribute together with hydrophobic interactions to the progressive chain arrangement into micelles and their consequent aggregation to finally form a gel (Aoki et al, 1994;Laurano et al, 2019). This high degree of physical crosslinking within SHP407 gel was probably also responsible for its lower resistance to applied deformation (γ L of 18.6 and 11.6% for NHP407 and SHP407 gels, respectively) and Yield Stress (YS of 1790 and 875 Pa for NHP407 and SHP407 gels, respectively) compared to NHP407-based one ( Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, at 37 • C both NHP407 and SHP407 systems exhibited ω G /G crossover values lower than 0.1 rad/s and turned out to be in the gel state, although a not complete gel development was achieved. This result can be correlated to the presence in SHP407-based system of a higher number of hydrogen bonds due to the exposure of free -NH 2 groups, which contribute together with hydrophobic interactions to the progressive chain arrangement into micelles and their consequent aggregation to finally form a gel (Aoki et al, 1994;Laurano et al, 2019). This high degree of physical crosslinking within SHP407 gel was probably also responsible for its lower resistance to applied deformation (γ L of 18.6 and 11.6% for NHP407 and SHP407 gels, respectively) and Yield Stress (YS of 1790 and 875 Pa for NHP407 and SHP407 gels, respectively) compared to NHP407-based one ( Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Laurano et al have recently reported a modified synthesis protocol resulting in the introduction along the backbone of a P407-based PEU of approximately 10E20 secondary amino groups/g PEU (Laurano et al, 2020). Another possible route to be investigated consists in adapting the plasma treatment protocol developed by Laurano et al (2019) to expose primary amines along polymer backbone using allylamine as monomer (Jeong et al, 2019) or ammonia gas (Mahmoudifard et al, 2017). In view of the final application of the developed formulation, SHP407 hydrogel injectability, dispersion and gelation in situ within an organism were demonstrated ex vivo using murine cadavers (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The P407-based poly(ether urethane) used in this work was synthesised following the pre-polymerisation method recently described by Laurano et al (2019) ( Supplementary Figure S1 ). Specifically, P407 was first dissolved in DCE (20% w/V concentration) at 80°C under continuous nitrogen flow.…”
Section: Methodsmentioning
confidence: 99%
“…Irrespective of the macrodiol used, both spectra showed the characteristic bands ascribed to newly formed urethane bonds, thus proving the success of the synthesis. Specifically, the bands at 1,720 cm −1 and 1,630 cm −1 can be ascribed to the stretching vibration of carbonyl groups; the band at 3,350 cm −1 can be attributed to the stretching vibration of N-H bonds, while at 1,540 cm −1 the spectrum showed the bending vibration band of N-H bonds together with the stretching vibration band of C-N bonds (Laurano et al, 2019;.…”
Section: Poly(ether Urethane) Chemical Characterizationmentioning
confidence: 96%